Essays on synergies from the geographic clustering of literary artists - Mitchell, Sara (Trinity College (Dublin, Ireland). Department of Economics, 2017)
This thesis consists of five chapters on synergies from the geographic clustering of literary artists. Chapter 1 provides an introduction to the thesis. Chapter 2 utilises a unique, purpose built panel dataset on prominent authors in the UK and Ireland born 1700-1925 to estimate the productivity gains associated with agglomeration of an industry with few capital requirements and no apparent need to cluster geographically. I analyse the patterns of migration and clustering of authors, and I construct age-productivity profiles to determine the productivity gains (if any) associated with the geographic clustering of literary activity. Individual fixed effects are utilised to control for spatial sorting by skill level, and the within estimator reveals the average author annual productivity is 10.68% per annum higher when the author resides in London, the only major literary cluster during the time period. There is no evidence of dynamic learning effects, and there is no evidence that the results are driven by a dynamic self-selection process.
Keywords: Economics, Ph.D.; PhD Trinity College Dublin, 2017